Literatur review: Peranan board connection dalam meningkatkan kinerja perusahaan - Variyetmi Wira (Jurnal Kajian Manajemen Bisnis, 2021)
TThis paper focuses on the systematic review related to literatures on board connection towards firm performance. The review utilizes the samples of 19 research articles published in 2015-2019 time period. The articles are taken in accordance with their journal’s outlet and publications, methodology and research theory, geography data, research concept, and research model. Taking into account, previous research regarding this matter is still limited, therefore it can be developed into broader geography and research concepts. The main theories used in this concept are agency theory, resource dependence theory, and neo-institutional theory. Notably, this paper explores the characteristics of corporate governance in the form of ownership structure, board characteristics, and board connection where they can interact with one to another and can influence the firm performance.Keywords: Board characteristic; board connection; corporate governance; literature review; ownership structure TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//